2016
DOI: 10.1002/ejoc.201600953
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physical‐Chemical Properties of cis‐ and trans‐1‐Amino‐3‐fluoro‐3‐methylcyclobutanecarboxylic Acids

Abstract: Hitherto unknown cis‐ and trans‐1‐amino‐3‐fluoro‐3‐methylcyclobutanecarboxylic acids were synthesized as pure diastereomers starting from diisopropyl 3‐oxocyclobutane‐1,1‐dicarboxylate. While pKa values of the carboxylic acid functions are the same for both stereoisomers (pKa = 2.80), the values for the amino groups are slightly different (8.46 or 8.77, respectively) presumably because of different interactions with the fluorine atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…Stereoselective access to cyclobutane and cyclobutane derived amino acids has been pursued by several groups [ [129] , [130] , [131] ]. One example was reported by Haufe and co-workers who disclosed the synthesis of cis‐and trans‐1‐amino‐3‐fluoro‐3‐methylcyclobutanecarboxylic acids in 2016 ( Scheme 36 ) [ 132 ]. Starting from the commerically available oxo-ester 178 , methylation using AlCl 3 was carried out to generate hydroxyl containing 179 in 69 % yield.…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stereoselective access to cyclobutane and cyclobutane derived amino acids has been pursued by several groups [ [129] , [130] , [131] ]. One example was reported by Haufe and co-workers who disclosed the synthesis of cis‐and trans‐1‐amino‐3‐fluoro‐3‐methylcyclobutanecarboxylic acids in 2016 ( Scheme 36 ) [ 132 ]. Starting from the commerically available oxo-ester 178 , methylation using AlCl 3 was carried out to generate hydroxyl containing 179 in 69 % yield.…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 99%
“…Interestingly it was found that the amino groups of the two stereiosomers of 184 displayed different basicities whilst the carboxylic acid moiteies of the same compound had identical basicity profiles.
Scheme 36 Synthesis of cis‐and trans‐1‐amino‐3‐fluoro‐3‐methylcyclobutanecarboxylic acids by Haufe and co-workers [ 132 ].
…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing our previous investigations on new 3-substituted cyclobutyl amines and amino acids, we present here multigram syntheses of other hitherto unknown α-aminocyclobutane carboxylic acids, 1-amino-3-hydroxy-3-methylcyclobutanecarboxylic acids cis - and trans -10 which can be considered as conformationally restricted analogues of threonine, where the rigid cyclobutane ring is a bioisostere of the C–C single bond (Figure ). Compounds cis - and trans - 10 are achiral due to the plane of symmetry while threonine contains two stereogenic centers.…”
mentioning
confidence: 92%
“…The synthesis started from commercially available ketoester 11 (Scheme ), which was methylated with AlMe 3 using a previously validated procedure . The following monohydrolysis proceeded stereoselectively: only the cis -monoester 13 was isolated in diastereomerically pure form.…”
mentioning
confidence: 99%